2020
DOI: 10.1038/s41416-020-0953-0
|View full text |Cite
|
Sign up to set email alerts
|

New tools to prevent cancer growth and spread: a ‘Clever’ approach

Abstract: Clever-1 (also known as Stabilin-1 and FEEL-1) is a scavenger receptor expressed on lymphatic endothelial cells, sinusoidal endothelial cells and immunosuppressive monocytes and macrophages. Its role in cancer growth and spread first became evident in Stab1-/knockout mice, which have smaller primary tumours and metastases. Subsequent studies in mice and humans have shown that immunotherapeutic blockade of Clever-1 can activate T-cell responses, and that this response is mainly mediated by a phenotypic change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 68 publications
(124 reference statements)
1
42
1
Order By: Relevance
“…This is consistent with the observation that mouse bladder wall injection with S. haematobium eggs leads to urothelial hyperplasia, a potentially be pre-cancerous state [17]. Proteins including metalloreductase (STEAP4) [40], platelet-activating factor acetylhydrolase (Pla2g7) [41], disabled homolog 2 (Dab2) [42], peptidyl-prolyl cis-trans isomerase (Fkbp14) [43], stabilin-1 (Stab1) [44,45], lysyl oxidase homolog 2 (Loxl2) [46], U4/U6 small nuclear ribonucleoprotein (Prpf3) [47], latent-transforming growth factor beta-binding protein (Ltbp3) [48], RNA-binding protein (Nob1) [49], isoform 1 of RNA-binding protein (Raly) [50], and probable glutathione peroxidase 8 (Gpx8) [51] are all expressed in many different malignant tissues, including bladder tissue, and are linked with increased cell proliferation, oncogenic properties, and poor cancer prognosis. This is in line with our observations, as all these proteins were more highly expressed in egg-injected mice bladder tissue.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the observation that mouse bladder wall injection with S. haematobium eggs leads to urothelial hyperplasia, a potentially be pre-cancerous state [17]. Proteins including metalloreductase (STEAP4) [40], platelet-activating factor acetylhydrolase (Pla2g7) [41], disabled homolog 2 (Dab2) [42], peptidyl-prolyl cis-trans isomerase (Fkbp14) [43], stabilin-1 (Stab1) [44,45], lysyl oxidase homolog 2 (Loxl2) [46], U4/U6 small nuclear ribonucleoprotein (Prpf3) [47], latent-transforming growth factor beta-binding protein (Ltbp3) [48], RNA-binding protein (Nob1) [49], isoform 1 of RNA-binding protein (Raly) [50], and probable glutathione peroxidase 8 (Gpx8) [51] are all expressed in many different malignant tissues, including bladder tissue, and are linked with increased cell proliferation, oncogenic properties, and poor cancer prognosis. This is in line with our observations, as all these proteins were more highly expressed in egg-injected mice bladder tissue.…”
Section: Discussionsupporting
confidence: 88%
“…However, if the expression difference we observed for GPR162 is partially attributable to a global change in methylation, this could suggest an altered reception of adrenergic signaling [61][62][63]. STAB1 (Stabilin 1; log 2 FC = -0.05) from the study of Koestler et al [7] encodes a scavenger receptor suggested to mark immunosuppressive monocytes and macrophages, where decreased expression appears to increase T cell antitumor cytotoxicity [64]. SKAP1 (Src kinase-associated phosphoprotein 1; log 2 FC = 0.07) from the gene set of Yang et al [8] encodes a T cell receptor adaptor protein and is a known EOC risk locus with a possible cell-autonomous role in EOC tumorigenesis [65].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, TECs were shown to promote regulatory T cell (Treg) accumulation via up-regulation of the lymphatic and vasculature endothelial receptor 1 (CLEVER-1); an abundance of CLEVER-1-positive macrophages support immunosuppression. It has been reported that tumor-induced CLEVER-1 expression in both macrophages and endothelial cell populations was required to support the growth of melanoma, and that the chief driver was the diminished expression of vascular E- and P-selectin, and accumulation of Tregs and M2 macrophages in the tumors induced by CLEVER-1 ( 27 , 28 ).…”
Section: Cells and Components Of The Tme Involved In Suppression Of The Anti-tumor Responsementioning
confidence: 99%